Seleksi Bakteri Asam Laktat dan Pemanfaatannya sebagai Starter pada Fermentasi Biji Sorgum: Selection of Lactic Acid Bacteria and its Application as Starter for Sorghum Grain Fermentation - Yuliana, Meta; Meryandini, Anja; Sunarti, Titi Candra (Departemen Biologi, Institut Pertanian Bogor, 2019)
This research aims is to find starter for sorghum fermentation and to observe its influence in fermentation process and tannin level in sorghum flour. Four isolates of Lactic Acid Bacteria were tested as starter for Numbu and Kawali sorghum grain fermentation. The criteria was the ability to produce acid and cell viability. The fermentation used four treatments in duplicates. The selected isolate was inoculated into dehulled and non-dehulled sorghum grain. The fermentation time were 0, 24, and 48 h. Analysis were pH, total acidity, total sugar, viable cell, tannin level, structure of sorghum flour, the yield of flour passed 80 mesh, and flour moisture. The results showed that E1222 was selected as a starter for Numbu sorghum grain fermentation while E5 was selected for Kawali. The starter can decrease pH value, increasing total acidity, decreasing total sugar, however there was no significant difference in viable cell in fermentation process. It decreased tannin level approximately 90% in Numbu fermented flour and 77% in Kawali. There was corrosion in starch structure of fermented flour, while the yield of flour passing through 80 mesh was increased. The best treatment was fermentation of dehulled and inoculated sorghum grain (So-St) in both of sorghum varieties.